2009
DOI: 10.1086/598331
|View full text |Cite
|
Sign up to set email alerts
|

Herpes Zoster Risk Factors in a National Cohort of Veterans with Rheumatoid Arthritis

Abstract: Background Herpes zoster occurs more commonly in patients taking immunosuppressive medications, though the risk associated with different medications is poorly understood. Methods Retrospective cohort study including 20,357 patients who were followed in the Veterans Affairs healthcare system and treated for rheumatoid arthritis from October 1998 through June 2005. Cox proportional hazards regression was used to determine risk factors for herpes zoster, and herpes zoster-free survival. Chart review was perfor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
185
2
7

Year Published

2011
2011
2016
2016

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 201 publications
(208 citation statements)
references
References 33 publications
14
185
2
7
Order By: Relevance
“…Enhanced pharmacovigilance for these events is therefore warranted. The IR for herpes zoster infection (serious and non-serious) was higher for tofacitinib [4.3 (95% CI: 3.83-4.90) per 100 patient-years] than the rates reported in the literature for patients with RA treated with biologic and nonbiologic DMARD (0.0034 to 2.4 events per 100 patient-years) 39,40,41,42,43,44,45,46 . It is noteworthy that the rates of herpes zoster in the phase III cohorts of patients receiving placebo and adalimumab in the tofacitinib program were also higher than those in the literature overall 47,48 .…”
Section: Rheumatologymentioning
confidence: 78%
“…Enhanced pharmacovigilance for these events is therefore warranted. The IR for herpes zoster infection (serious and non-serious) was higher for tofacitinib [4.3 (95% CI: 3.83-4.90) per 100 patient-years] than the rates reported in the literature for patients with RA treated with biologic and nonbiologic DMARD (0.0034 to 2.4 events per 100 patient-years) 39,40,41,42,43,44,45,46 . It is noteworthy that the rates of herpes zoster in the phase III cohorts of patients receiving placebo and adalimumab in the tofacitinib program were also higher than those in the literature overall 47,48 .…”
Section: Rheumatologymentioning
confidence: 78%
“…We located 4 observational studies providing evidence on the comparative risk of varicella zoster virus infections (herpes zoster or shingles) in over 45,000 RA patients receiving adalimumab, etanercept, and infliximab (32,(40)(41)(42). In an analysis of 11,881 patients from a British registry, a significantly higher risk of herpes zoster with infliximab was observed when compared with adalimumab (HR 1.5, 95% CI 1.1-2.0) (32).…”
Section: Resultsmentioning
confidence: 99%
“…However, a large US study including 21,817 patients with RA reported no difference in the risk of herpes zoster in the initiators of these 3 agents (aHR for adalimumab versus infliximab 0.85, 95% CI 0.55-1.22 and for etanercept versus infliximab 1.09, 95% CI 0.82-1.45) (40). In another study conducted in patients from the Department of Veterans Affairs, authors did not directly compare the 3 agents head-to-head but concluded that etanercept and adalimumab were associated with lower risk of herpes zoster than (41). One study did not conduct formal statistical comparison between individual TIMs but did report crude rate (95% CI) of herpes zoster as 8.9 (5.6-13.3) per 1,000 person-years in the etanercept group and 11.1 (7.9-15.1) per 1,000 person-years in the adalimumab/infliximab combined group (42).…”
Section: Resultsmentioning
confidence: 99%
“…В другом ретроспек-тивном когортном исследовании встречаемость Herpes zoster (HZ) у больных РА составила 9,96 эпизодов на 1 000 пациенто-лет. Независимые факторы риска развития инфекции включали пожилой возраст, применение пред-низолона, цитотоксических препаратов и иФНО-α, нали-чие онкопатологии, хронические заболевания легких, недостаточность функции печени и почек [89]. В рамках германского регистра биологических препаратов HZ-инфекция у больных РА, получавших иФНО-α, развива-лась достоверно чаще, чем при использовании БПВП (10,1 и 5,6 случаев на 1000 пациенто-лет соответственно, р=0,01).…”
Section: эксперты международных и национальных научных ревматологичесunclassified